2018
DOI: 10.5888/pcd15.180190
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, Beliefs, and Cost-Related Medication Nonadherence Among Adults Aged 65 or Older With Chronic Diseases

Abstract: IntroductionCost-related medication nonadherence (CRN) can negatively affect chronic disease prevention and management in an aging population. Limited data are available on the interacting influences among such factors as availability of financial resources, attitudes and beliefs of patients, and CRN. The objective of this study was to examine the causal paths among financial resource availability, patient attitudes and beliefs, and CRN.MethodsWe used a nationally representative sample (n = 4,818) from the 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 28 publications
1
23
1
3
Order By: Relevance
“…This study is unique in that it employed four measures of financial hardship directly related to diabetes outcomes: difficulty paying bills, food insecurity, medication cost nonadherence, and ongoing financial strain. While prior research found a relationship between cost-related medication nonadherence and outcomes in diabetes (Berkowitz et al, 2014, 2015; Kang et al, 2018; Lee et al, 2018; Ngo-Metzger et al, 2012; Williams et al, 2013; Zhang et al, 2014) this is one of the first studies to highlight the importance, from a health standpoint, of understanding if older adults with diabetes are struggling with paying bills (Levy, 2015; Simons et al, 2016). In addition, by investigating a count of financial hardship measures, we found a cumulative relationship with glycemic control.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This study is unique in that it employed four measures of financial hardship directly related to diabetes outcomes: difficulty paying bills, food insecurity, medication cost nonadherence, and ongoing financial strain. While prior research found a relationship between cost-related medication nonadherence and outcomes in diabetes (Berkowitz et al, 2014, 2015; Kang et al, 2018; Lee et al, 2018; Ngo-Metzger et al, 2012; Williams et al, 2013; Zhang et al, 2014) this is one of the first studies to highlight the importance, from a health standpoint, of understanding if older adults with diabetes are struggling with paying bills (Levy, 2015; Simons et al, 2016). In addition, by investigating a count of financial hardship measures, we found a cumulative relationship with glycemic control.…”
Section: Discussionmentioning
confidence: 90%
“…Individuals living with diabetes and high financial needs report the necessity of cost trade-offs such as decreased food intake and cutting down on medication to control their diabetes (Billimek & Sorkin, 2012; Silverman et al, 2015). These necessary decisions have health consequences; for instance, cost-related medication underuse is associated with poor diabetes control and increased emergency room (ER)/inpatient visits (Berkowitz et al, 2015; Kang et al, 2018; Lee et al, 2018). Although many studies find younger adults have higher risk for cost-related nonadherence, often based on lack of insurance, a study of adults with Medicare Part D coverage found high rates of cost-related nonadherence particularly in cardiometabolic medications (Ngo-Metzger et al, 2012; Williams et al, 2013; Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…7 Further, medication nonadherence, along with suboptimal prescribing and drug administration, results in $290 billion in avoidable medical spending annually in the United States. 8 Older adults, aged 65 years or older, with multiple chronic conditions face medication nonadherence, 9,10 and such nonadherence is associated with potentially avoidable health services use. 8,11 For example, previous studies found that medication adherence rates among patients with at least one chronic condition can be as low as 50%, 12,13 and nearly 15% of chronically ill Americans specifically stated that costs were the main reason for medication underuse.…”
mentioning
confidence: 99%
“…Interestingly, approximately half of the sample disclosed being nonadherent to prescribed medications, and slightly more than a quarter of the sample was affected by any cost-related nonadherence ( Wilson et al, 2007 ). This phenomenon is known as cost-related medication non-adherence (CRN) impacting vulnerable populations such as older adults ( Briesacher, Gurwitz, & Soumerai, 2007 ; Lee, Jiang, Dowdy, Hong, & Ory, 2018 ). With the rising cost of drugs, individuals are forgoing treatment (skipping doses, splitting pills, delaying or stopping fills, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…With the rising cost of drugs, individuals are forgoing treatment (skipping doses, splitting pills, delaying or stopping fills, etc.) as they are unable to afford needed medications ( Lee et al, 2018 ). As medications are a cornerstone of condition management, medication nonadherence may exacerbate conditions and lead to poor health outcomes with increased risk of downstream complications.…”
Section: Introductionmentioning
confidence: 99%